Implementing Nature-Based Self-Grounding Techniques as an Alternative Therapy for Elementary School Children with Sensory Problem in Homeschool Total Mind Learning (TML) - Fitri Meliani; Shofiyyah Shofiyyah; Putri Anindita Pratiwi; Yuriska Dewi Suwarno (LJPI UI Bunga Bangsa Cirebon, 2026)
Objective: This study explores the implementation of nature-based self-grounding techniques as an alternative therapeutic approach for elementary school children with sensory problems at Homeschool Total Mind Learning (TML). Novelty: The study emphasizes the use of nature-based self-grounding activities within the Homeschool Total Mind Learning (TML) approach as an alternative therapy for children with sensory problems, highlighting direct interaction with natural environments to support sensory integration, emotional regulation, and adaptive functioning. Methods: Using a qualitative approach, data were collected through interviews with three parents and two teachers. The implemented activities included walking barefoot in gardens, playing in rice fields, climbing hills, herding livestock, and participating in farming activities. The analysis was guided by A. Jean Ayres’s Sensory Integration Theory, particularly concerning tactile and proprioceptive stimulation. Results: The findings reveal that nature-based self-grounding activities provide meaningful sensory experiences that help improve children’s emotional regulation and adaptive behavior. Parents reported reduced meltdowns and increased sensory tolerance, while teachers observed better focus, classroom participation, and social interaction. Furthermore, the children showed greater self-awareness and independence in managing their sensory needs. Conclusion: This study concludes that implementing nature-based self-grounding techniques can serve as an effective alternative therapy for supporting sensory development and improving the quality of life and adaptive functioning of elementary school children with sensory problems in homeschooling contexts.